1984
DOI: 10.2166/nh.1984.0008
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a Model of Snow Cover Area versus Runoff against a Concurrent Flow Correlation Model in the Western Himalayas

Abstract: This study evaluates the estimates of seasonal snowmelt runoff in the Sutlej, Indus, Kabul and Chenab rivers derived from the model of snow cover area vs. runoff against those obtained from cross correlation of concurrent flows in the rivers. The concurrent flow correlation model explains more than 90 percent of the variability in flow of these rivers. Compared to this model, the model of snow-cover area vs. runoff explains less of the variability in flow. However, unlike the snow-cover model, the concurrent f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Acceptance of these two transformed linear regressions would, however, require explanation of the functional relationship between snowmelt and snow cover area by two hypotheses. Such a proposition does not appear to be consistent with reality since the Himalayan watersheds reportedly are characteristic of innate concurrent flow conditions during the melt season (Dey and Goswami 1984).…”
Section: Resultsmentioning
confidence: 90%
“…Acceptance of these two transformed linear regressions would, however, require explanation of the functional relationship between snowmelt and snow cover area by two hypotheses. Such a proposition does not appear to be consistent with reality since the Himalayan watersheds reportedly are characteristic of innate concurrent flow conditions during the melt season (Dey and Goswami 1984).…”
Section: Resultsmentioning
confidence: 90%
“…These simple relationships worked well for some applications and particularly in data-sparse regions of the world. Estimation of daily snow melt runoff in the Himalayan river basins using satellite-derived SCA is being increasingly recognized as an immensely useful procedure in water resources research and management (Rango et al 1977;Ramamoorthi and Subba Rao 1981;Gupta et al 1982;Dey et al 1983Dey et al , 1989Dey and Goswami 1984;Jain 2001). The prediction of snow melt induced runoff in the Himalayan rivers has a great potential for application in irrigation, hydropower generation, and domestic and industrial water supply.…”
Section: Introductionmentioning
confidence: 99%
“…Gupta et al (1982) reported that the snow-covered area and the subsequent snowmelt runoff in various sub-catchments in the Himalayan region are found to be well correlated. Later, snow-covered area was used for daily runoff simulation (Dey & Goswami, 1984;Dey et al, 1989;Jain, 2001). Singh & Jain (2002) used snow-covered area to estimate the contribution from snowmelt runoff to annual flows using a water balance approach.…”
Section: Introductionmentioning
confidence: 99%